Hubungan Antara Pola Asuh Otoriter Dengan Perilaku Bullying Pada Siswa Smp N 24 Surakarta - Adi Purnama, Bagus; , Taufik, S.Psi, M.Si, Ph.D (2017)
The existing problems based on the results of interviews in junior high school in a city surakarta suspected happened behavior bullying. Researcher has conducted interviews with one of the students with the as follows, That this school bullying often happens because trifles as hit friends or nudging accidentally , mutual mock each other and lead fights among students. The purposes of this research are: 1). To know the correlation between authoritarian parenting pattern and the behavior of bullying in the students of SMP N 24 Surakarta. 2). To know the effective contribution of authoritarian parenting pattern on the behavior of bullying. 3). To know the level of authoritarian parenting pattern in the students. 4). To know the behavior of bullying in the students. Hypothesis proposed was that there is a positive correlation between the authoritarian parenting pattern and the behavior of bullying in the students. Subjects in the research were as many as 70 subjects. Population used in this research was the students in the age of 12-15 years old in SMP N 24 Surkarta. Meanwhile, the measurement used in this research are: a). Scale of authoritarian parenting pattern and b). Scale of the behavior of bullying. The technique of data analysis used in this research was correlation of product moment. The conclusion of the hypothesis was that there was a very significantly positive correlation between the authoritarian parenting pattern and the behavior of bullying in the students of SMP N 24 Surakarta. The higher the authoritarian parenting pattern, the higher the behavior of bullying will be, on the contrary, the lower the authoritarian parenting pattern, the lower the behavior of bullying will be. It was revealed by the score of r=319 with sig. 0,004; (p < 0,01). The level of authoritarian parenting pattern of the subject was categorized as low. The behavior of bullying in the subject was categorized as low. It was revealed by the empirical mean as much as 54.10 and hypothetical mean as much as 77.5. The effective contribution of the authoritarian parenting pattern was as much as 10.17 %. It still revealed that there was 89.83 % of other variables which can influence the behavior of bullying outside the variable of authoritarian parenting pattern.